DAMPAK EKONOMI DAN SOSIAL BUDAYA PEMBANGKIT LISTRIK TENAGA UAP (PLTU) TERHADAP MASYARAKAT DI GAMPONG SUAK PUNTONG KABUPATEN NAGAN RAYA - Triyanto Triyanto (Jurnal Community, 2017)
Anything that is in around of human society always has an influence on the human himself. Similarly, the existence of a steam power plant (PLTU) located in Gampong Suak Puntong Nagan Raya. According to preliminary observations, researcher founds data on the existence of steam power plants have worried the community where some buildings are cracked due to the vibration of the soil during construction, heated air, dust, and wastewater suspected to be the cause of the disease. However, this study examines its impact from an economic and socio-cultural point of view. The formulation of the problem are how is the influence of the existence of PLTU to welfare? and how is the influence of the existence of PLTU to socio-cultural life?.The results showed that PLTU has an effect on improving people's welfare in Suak Puntong. This is proved by Pearson Chi-Square value in Asymp column. Sig. lower than 0.05 so that H0 is rejected and H1 accepted. While the power plant has no influence on the socio-cultural life of the community, this is proved by the value of Pearson Chi-Square in all tables in the Asymp column. Sig. Higher than 0.05, except for the Chi-Square Tests in the steam power plant that had assisted in the construction of the mosque against the religious activities of the community worth 0.000 and less than 0.05. But in general the value of Chi-Square Tests is higher than 0.05 so that H0 is accepted and H1 is rejected.Keywords: PLTU, Suak Puntong, Nagan Raya, Social Culture,